"It is not O.K to think that you are good just because you have graduated from overseas": Agency and contextual factors affecting Vietnamese returning graduates. (21st January 2022) - Tran, Ly Thi; Bui, Huyen; Tan, George; Rahimi, Mark
Abstract: Over the past decade, a growing number of graduates, originally from key source countries of international students such as China and Viet Nam, have returned home after graduation from overseas universities. In particular, there seems to be a recent surge in the number of international graduates heading home due to the high unemployment, tightening migration, rising national protectionism and emerging challenges, exacerbated by the COVID‐19 pandemic, in major host countries such as Australia, the UK and the United States. While there has been emerging empirical research on international returning graduates' contributions to their home country development, little is known about graduates' own perceptions of the impacts of the contextual factors on their homecoming decision and their home labour market navigation. Draving on a qualitative study, this article responds to this critical gap in the literature by conceptualising returnee employability as a dynamic interactive process between multiple forces in the host and home labour markets and broader socio‐economic contexts, and between these forces and returnee agency . It identified interrelated contextual factors in the host and home contexts that drive Vietnamese graduates home, including challenges in securing migration, and insecure job prospects facing them in Australia and simultaneously, greater employment and business opportunities at home. In particular, the study found that contextual factors such as sector characteristics, types of employers, economic performance and cultural practices create an institutional environment, in which returnees' agency is enacted, resulting in different returnees' labour market navigation experiences and employment outcomes. Significant recommendations for key stakeholders in both home and host countries to support international graduate employability are provided.